Antigen B modulates anti‐inflammatory cytokines in the EAE model of multiple sclerosis. Issue 2 (29th December 2022) - Mariki, Aliakbar; Barzin, Zahra; Fasihi Harandi, Majid; Karbasi Ravari, Kimia; Davoodi, Mahboubeh; Mousavi, Seyed Mohammad; Rezakhani, Soheila; Nazeri, Masoud; Shabani, Mohammad
Abstract: Introduction: : Multiple sclerosis (MS) is characterized by the destruction of the blood–brain barrier, loss of myelin sheath, and contribution of inflammatory interleukins such as TNF‐alpha, interleukin‐17, and interleukin‐6. Methods: : The current study investigated the effect of antigen B of hydatid cyst fluid on the reduction of anti‐inflammatory cytokines and nerve conduction velocity in rats with experimental autoimmune encephalomyelitis (EAE)‐induced MS. After isolation of antigen B from sterile cyst fluid, the rats were randomly divided into four groups: saline, EAE, EAE + teriflunomide (EAE + TF), and EAE + antigen B (EAE + AngB). The EAE model was induced using cow spinal cord homogenization, in combination with Freund's complete adjuvant. The serum concentration of cytokines including IL‐1B and IL‐17, IL‐10, IL‐6, and TNF‐X was measured by the ELISA method, and real‐time PCR was performed to study gene expression. Electrophysiological, behavioral, and neuropathological tests were also conducted. Results: : Nerve conduction velocity and IL‐10 concentration were increased in the antigen B group. The results of this study showed that antigen B reduced the inflammatory component of the EAE MS animal model by modulating the immune system compared to teriflunomide, which eventually led to a reduction in symptoms at the behavioral and electrophysiological level. Conclusions: : It seems that antigen B plays a critical role in regulating immunity and it can be used as a possible therapeutic agent to modulate the immune system in MS patients. It might be rational to consider hydatid cyst fluid antigen as a modifier in MS.